Początki Kolegium Polskiego w Rzymie w XVI i XVII w. oraz działania zmierzające do jego utworzenia w XIX w. - Stępień, Marek (Prawo Kanoniczne, 2010)
After the Council of Trent during the pontificate of the Pope Gregory XII (15721585), the numerous colleges, the seminaries for priests educating future clergy, were being established in Rome. During those times the established colleges were as follows: German-Hungarian in 1552, Greek in 1577, English in 1579, Marians in 1584 (marionickie). Polish college was established after receiving papal approval at 1 September 1582 by Philippe Nereusz and existed only by the end of 1586. In the middle of the XVII century Polish King Jan Kazimierz created with papal approval Polish-Swedish college. The new institution remaining under the Polish King supervision from Waza dynasty and was destined for Polish and Swedes. Unfortunately, after the death of Jan Kazimierz the college was supervised by the Swedish Queen Kristina, who decided that the college would be destined only for Swedes. Through the following two hundred years there were not any centre educating Polish clergy. In the middle of the XIX century Bogdan Jański together with his friends and monks Peter Semeneka and Hieronim Kajsiewicz, the founders of the Congregation of the Ressurectionist Fathers, started the efforts leading to reestablishing the Polish College in Rome, that would educate and prepare the candidates for priesthood. The funds were gathered remembering about convincing the Pope to this initiative.